2023
DOI: 10.3390/su151712869
|View full text |Cite
|
Sign up to set email alerts
|

Learning Models for Higher Education in Engineering: Motivation, Self-Determination, and the Role of Information and Communication Technologies

Ana Bustamante-Mora,
Mauricio Diéguez-Rebolledo,
Yemsy Hormazábal
et al.

Abstract: In the last decade, great strides have been made to increase access to education and enrollment rates at all levels (primary, secondary, and higher education). Actions such as promoting equal access to education, preventing school dropout, and establishing free education, among other actions proposed by organizations such as UNESCO, seek to guarantee the universality of education. This is undoubtedly a great challenge, and to address it, it is necessary to characterize how students face the learning process, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 147 publications
0
3
0
Order By: Relevance
“…It was found that positive technology-enhanced learning provides cadets with flexibility and makes learning more personalized (Ivanović et al, 2018). Bustamante-Mora et al (2023) stated that using a technology-enhanced learning environment in military engineering education contributes to the increase of learners' interest and motivation to professional activities. Spridzāns (2023) and Smith et al (2021) insisted that digital technologies facilitate cadets' collaboration and make the educational process interactive.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that positive technology-enhanced learning provides cadets with flexibility and makes learning more personalized (Ivanović et al, 2018). Bustamante-Mora et al (2023) stated that using a technology-enhanced learning environment in military engineering education contributes to the increase of learners' interest and motivation to professional activities. Spridzāns (2023) and Smith et al (2021) insisted that digital technologies facilitate cadets' collaboration and make the educational process interactive.…”
Section: Discussionmentioning
confidence: 99%
“…Grierson states that an organized compilation of bibliographic citations and abstracts of the civil and structural engineering design literature contains some of the most complete scientific and engineering publications in the world [7]. Bustamante‐Mora et al analyze learning models, motivation, self‐determination, and technology used for learning achievement in higher education engineering education and suggest best practices for using learning models, strategies, and information and communication technologies to foster intrinsic motivation in students [2]. Wang et al point out the main challenges and future research directions for artificial intelligence (AI)‐based computational analysis in civil engineering by reviewing recent advances in research on the use of AI techniques for material and structural analysis in civil engineering, describing the relevant applications, discussing the strengths and weaknesses of the current research, and presenting specific examples [23].…”
Section: Introductionmentioning
confidence: 99%
“…Securing fair access for individuals seeking top-notch education to improve their learning and job prospects is a fundamental goal of the global development strategies [1,2]. In 2015, the United Nations introduced 17 Sustainable Development Goals (SDGs) to address critical global social, environmental, and economic issues [3,4].…”
Section: Introductionmentioning
confidence: 99%